Absolute Dimensions of the Interferometric Binary HD 174881: A Test of Stellar Evolution Models for Evolved Stars - Guillermo Torres; Andrew F. Boden; John D. Monnier; Gerard T. van Belle (The Astrophysical Journal)
We report high-resolution spectroscopic monitoring and long-baseline interferometric observations with the Palomar Testbed Interferometer (PTI) of the 215 day binary system HD 174881 (K1 II-III), composed of two giant stars. The system is spatially resolved with the PTI, as well as in archival measurements with the CHARA Array. Our analysis of these observations, along with an analysis of the spectral energy distribution, have allowed us to infer accurate values for the absolute masses ( ${3.367}_{-0.041}^{+0.045}$ and ${3.476}_{-0.043}^{+0.043}\,M_{\odot }$ ), radii (34.0 ± 1.3 and 22.7 ± 1.8 R _☉ ), effective temperatures (4620 ± 100 and 4880 ± 150 K), and bolometric luminosities of both components, as well as other properties including the orbital parallax (distance). These provide valuable tests of stellar evolution models for evolved stars, which are still relatively uncommon compared to the situation for main-sequence stars. We find generally good agreement of all of these properties of HD 174881 with two sets of recent models (MIST and PARSEC) at compositions near solar, for ages of 255–273 Myr. We also find evidence of an infrared excess, based largely on the flux measurements from IRAS at 60 and 100 μ m.